Celtic cleruchs in Greece: Some Case Studies - Ciarini, Alessio (ARYS. Antigüedad: Religiones y Sociedades, 2025)
The contacts between the Celts and the Greek world during the Hellenistic were multifaceted: beyond sporadic invasions and raids, these populations more often traded and collaborated peacefully with the Greek-Macedonian states, sometimes even managing to integrate into their society. For instance, many Gallic mercenaries obtained grants of land to settle on at the end of their careers. While there is evidence of these military colonists in the territories of the Eastern Hellenistic kingdoms, the same cannot be said for Antigonid Macedonia, where evidence is scarce. This study aims to outline three possible cases in which Gallic mercenaries may have been settled as cleruchs by Macedonian rulers in Greek territory.
Keywords: Celts; Mercenaries; Cohabitation; Antigonids; Hellenistic Religion